A Nordic transition regime? Policies for school-to-work transitions in Sweden, Denmark and Finland. (May 2019) - Helms Jørgensen, Christian; Järvinen, Tero; Lundahl, Lisbeth
In recent decades, a range of policy measures to support young people's school-to-work transitions has been initiated across Europe. However, these transition policies have rarely been studied systematically, particularly from a comparative perspective. Thus, the aim of this article is to compare Swedish, Danish and Finnish policies for supporting young people's educational and school-to-work transitions. Synthesising and analysing recent research, the article critically draws on Walther's (2006) classification of transition regimes that recognises a Nordic universalistic regime of youth transitions characterised by emphasis on collective social responsibility, individual motivation and personal development. We conclude that significant policy changes have occurred during the last two decades. Coercive measures have been adopted and social support reduced, making young people more individually responsible for the success of their transitions. Hence, current transition policies diverge in many respects from qualities traditionally ascribed to the Nordic transition regime. We also find significant differences between the three countries' transition policies, which in some cases indicate policy trade-offs. In addition, we conclude that transition policies are generally weakly coordinated across policy domains, which increases the risk of unintended consequences of these policies.